The Influence of Audit Quality and Profitability on Profit Management with Good Corporate Governance as Moderation in Construction Companies Listed on the Indonesia Stock Exchange (BEI) - Junidwan, Alditra Dwiky; Purba, Rahima Br; Tripriyono, Agus (Asian Journal of Management Analytics, 2024)
By using this research, we try to test empirically, using good corporate governance as a moderating variable, how much influence audit quality and profitability have on earnings management in construction companies listed on the Indonesia Stock Exchange between 2018 and 2022. After five years of observation, the sample consisted of 21 companies obtained through purposive sampling, resulting in a total of 105 data points for this lesson. We used Eviews 9 to perform panel data regression analysis, goodness of fit tests, and classical assumption tests. According to research, audit quality and profitability influence earnings management in construction companies listed on the Indonesia Stock Exchange for the 2018–2022 period. Trade. Taken together, audit quality and profitability impact the earnings management of public construction companies.